Voice-Over for Animation - Wright, Jean; Lallo, M. J. (Routledge, 2013)
Voice Over for Animation takes animation and voice-over students and professionals alike through the animated voice-over world. The book provides information, exercises, and advice from professional voice-over artists. Now you can develop your own unique characters, and learn techniques to exercise your own voice gain the versatility you need to compete. You can also learn how to make a professional sounding demo CD, and find work in the field. Author MJ Lallo opened her own studio in 2000. She is a VO artist, director, producer, and casting director, casting from her own VO roster. She teaches VO as well and hires pros in the industry to guest direct. She just cast a video game for DreamWorks and also cast and contributed character reads to a Houghton-Mifflin American history book. The accompanying CD is professionally recorded, and features: 1. Improvization in character development 2. Examples of how to make an animation demo from beginning to final product. 3. Adapting your characters to animation scripts 4. Animation Talent Agent interviews 5. Casting Director interviews 6. Interviews with Animation Voice-Over Artists a. Nancy Cartwright (Bart, The Simpsons) b. Cathy Cavadini (Blossom, Power Puff Girls) c. Bill Farmer (Goofy)